Local NMDA receptor hypofunction evokes generalized effects on gamma and high-frequency oscillations and behavior. (1st September 2017) - Lee, Jaime; Hudson, Matthew R.; O'Brien, Terence J.; Nithianantharajah, Jess; Jones, Nigel C.
Highlights: MK801 elevates gamma (30–80 Hz) and high high-frequency oscillations (HFO). Local MK801 infusion increases oscillations in local circuits and in distant regions. Locomotion and stereotypy increase after infusion of MK801 into the PFC HIPP and NAcc. Abstract: The NMDA receptor (NMDAr) hypofunction theory of schizophrenia suggests that aberrant signaling through NMDAr underlies the pathophysiology of this disease. This is commonly modeled in rodents via treatment with NMDAr antagonists, which causes a range of behavioral effects that represent endophenotypes related to schizophrenia. These drugs also disrupt high-frequency neural oscillations within the brain, also potentially relevant to disease. We studied the effect of localized NMDAr hypofunction on the generation of neural oscillations occurring both locally and in distant brain regions, and on behaviors routinely used as endophenotypes to model psychosis in rodents. Wistar rats were implanted with local field potential recording electrodes in the prefrontal cortex, dorsal hippocampus and nucleus accumbens, as well as cannulae in these regions to facilitate drug infusion. Rats received bilateral infusions of MK801 (0, 5 μg, 20 μg, 50 μg) into one of the three target regions and their behavior measured in an open field. We also assessed the effects of systemic MK801 injection (0.16 mg/kg sc). Electrophysiological signals were recorded continuously, allowing assessment of gamma oscillations (30–80 Hz) and high-frequency oscillations (HFO: 130–180 Hz) occurring as a result of infusions. Regardless of MK801 infusion location, gamma oscillations and HFOs significantly and consistently increased in all three regions studied, similar to that observed following systemic injection. Locomotor activity, stereotypies and ataxia were also observed following infusion into all regions. We conclude that localized regions exhibiting NMDAr hypofunction are sufficient to disrupt local as well as diffuse neural circuits and global brain function, and concomitantly cause psychosis-related behavioral effects.